Harm Principle e direito penal : em busca da identificação de limites ao crime de lavagem de dinheiro - Machado, Tomás Grings (2017)
This study presents the basic problematization about the limits that the crime of money laundering presents and, more precisely, where or from which theoretical referential we can indicate the limits of the crime of money laundering. In an attempt to limit criminal law, traditional doctrine recognizes that, at least in the context of continental and brazilian doctrine, a crime is legitimately constituted when the criminalization of behavior represents an offense against a criminal legal good. The thesis presented here is based on the premise that the limit of the money laundering crime can not be rooted in the concept of criminal legal good and any attempt to adapt or even update this concept ends up challenging the very definition of criminal legal good. It discusses the reference of the concept of criminal legal good as a limit to criminal law, opposing it to the framework proposed by the common law context from the referential of harm to other principle. It is observed that the concept of criminal legal good is insufficient to identify the limits of the crime of money laundering, or it appears too broad, and thus does not carry any limitation, or it is too restrictive, and thus does not allow an effective adjustment to the purposes that lead to the criminalization of money laundering. It is verified that the application of harm to other principle presents itself as a more adequate mechanism for an effective limitation as to the dogmatic structure of the crime of money laundering.